Orofacial pain guidelines for assessment, diagnosis, and management - de Leeuw, Reny; Klasser, Gary D. ([S.l.] : Quintessence Publishing Co, Inc., 2019)
The AAOP Guidelines for Assessment, Diagnosis, and Management of Orofacial Pain is an invaluable resource for all health care professionals who evaluate and treat patients with orofacial pain and face the daunting task of keeping up with the literature in the rapidly emerging arena of pain management in clinical practice. This new edition continues to emphasize evidence-based knowledge and, for the first time, offers a summary of key points at the beginning of each chapter. Other important changes include an entirely new chapter on sleep and its relationship to pain and well-being; new imaging guidelines for the diagnosis of headache, TMD, and neuropathic pain; a new section on dysesthesias related to neuropathic pain; comprehensive descriptions of SUNCT/SUNA in the chapter devoted to primary headache disorders; and recommendations for quantitative sensory testing, narcotic agreement, and brief screening questionnaires used in patient assessment. Most important, the differential diagnosis and TMD chapters reflect the recommendations of the long-awaited RDC/TMD taxonomy, which will have a significant impact on clinical practice.
Orofacial pain : guidelines for assessment, diagnosis, and management, sixth edition -- Contents -- Preface -- 1. Introduction to Orofacial Pain -- 2. General Assessment of the Orofacial Pain Patient -- 3. Diagnostic Classification of Orofacial Pain -- 4. Vascular and Nonvascular Intracranial Causes of Orofacial Pain -- 5. Primary Headache Disorders -- 6. europathic Pain -- 7. Intraoral Pain Disorders -- 8. Differential Diagnosis and Management of TMDs -- 9. Cervical Spinal Disorders and Headaches -- 10. Extracranial and Systemic Causes of Head and Facial Pain -- 11. Sleep and Orofacial Pain -- 12. Axis II: Biobehavioral Considerations -- Glossary -- Index.
Includes bibliographical references and index.
Keywords: Facial Pain; Headache; Pain Measurement; Pain Management